P204‐mediated innate antiviral responses in mouse adipose cells and their effects on cell functions. Issue 2 (7th October 2014) - Yu, Lili; Liu, Peng; Liu, Zhenghui; Zhu, Weiwei; Yan, Keqin; Chen, Qiaoyuan; Han, Daishu
Abstract : Viruses can infect adipose tissues. However, innate antiviral responses in adipose cells and their effects on adipocyte function have not yet been intensively investigated. In this study, p204‐initiated innate antiviral responses in mouse adipose cells were examined. Cytosolic DNA sensor p204 and its signaling adaptor stimulator of interferon (IFN) genes (STING) were constitutively expressed in primary preadipocytes. Synthetic herpes simplex viral DNA (HSV60), a p204 ligand, induced type I IFN expression by activating IFN regulatory factor 3. Major antiviral proteins, including IFN‐stimulating gene 15, 2′, 5′‐oligoadenylate synthetase and Mx GTPase 1, in preadipocytes were upregulated by HSV60. HSV60‐triggered innate antiviral responses were significantly reduced by inhibition of p204 signaling with specific small interfering RNA targeting p204 or STING. HSV60 inhibited the differentiation of preadipocytes to mature adipocytes and enhanced the proliferation of adipose cells. Moreover, HSV60 induced innate antiviral responses in mature adipocytes and inhibited expressions of several adipokines, including leptin, adiponectin and resistin. These results indicated that p204 initiated innate antiviral responses in adipose cells, thereby modulating adipocyte function.